COMPARISON OF ANALYSIS METHODS FOR CURCUMIN DETERMINATION: A LITERATURE REVIEW - Jajang Japar Sodik; Deden Indra Dinata; R. Herni Kusriani; Garnadi Jafar (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Curcuminoids such as curcumin, demethoxycurcumin (DMC), and bisdemethoxycurcumin (BDMC) are the major bioactive components found in Curcuma species, including turmeric (Curcuma longa L.). Curcumin is a polyphenol that is used as an antioxidant. Various analytical methods have been developed for the detection of curcumin, each with its advantages and limitations. Selection of an appropriate analytical method is crucial for obtaining accurate results. Although critical reviews on the chemical, biological, and pharmacological properties of curcumin are widely available, reviews specifically focusing on the different analytical methods for curcumin are limited. This review article aims to provide an overview of several analytical methods for the determination of curcumin. This is expected to encourage readers to choose a suitable analytical method for their specific needs. The articles used in this review were sourced from international English-language publications obtained from Science Direct, PubMed, and Google Scholar. The search was performed using keywords such as